Resolving Fishing Disputes in Lubuk Larangan in Kuantan Singingi, Riau Province - Firmanda, Hengki; Supaat, Dina Imam; Wafi, Mahmud Hibatul; Sudjito, Sudjito; Lestari, Rika (Jurnal IUS Kajian Hukum dan Keadilan, 2023)
This research aims to explain the rules of management of lubuk larangan in Kuantan Singingi, and formulate the settlement of fishing disputes at lubuk larangan in Kuantan Singingi. This research is sociological legal research. The research location is the villages where there are lubuk larangan in Kuantan Singingi Regency, namely lubuk larangan in Indarung Muara Lembu Subdistrict, lubuk larangan in Bandar Alai Kari Village, Kuantan Tengah Subdistrict, and lubuk larangan in Lubuk Jambi, Kuantan Mudik Subdistrict. Informants in this research include Customary Chiefs in Indarung Muara Lembu Subdistrict, Bandar Alai Kari Village, Central Kuantan Subdistrict, and in Lubuk Jambi, Kuantan Mudik Subdistrict, as well as the Chairman of the Kuantan Singingi Customary Institution. This research shows that the rules for managing lubuk larangan in Kuantan Singingi from three research locations differ in the way they are managed. Lubuk Larangan in Indarung is managed jointly and controlled by traditional leaders. Settlement of fishing disputes in lubuk larangan in Kuantan Singingi is carried out through a customary process led by the customary leader. If the offenders are traditional leaders, they can be sanctioned twice harder compared to ordinary people.